2002
DOI: 10.1055/s-2002-32551
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic ent-Kaurane Diterpenoids from Isodon eriocalyx var. laxiflora

Abstract: Three new ent-kaurane diterpenoids laxiflorin E (1), laxiflorin H (6) and laxiflorin I (8) were isolated from the leaves of Isodon eriocalyx var. laxiflora, along with nine known diterpenoids, eriocalyxin A (2), laxiflorin C (3), laxiflorin D (4), laxiflorin A (5), maoecrystal S (7), maoecrystal Q (9), eriocalyxin B (10), maoecrystal C (11) and enmelol (12). The structures of the new compounds were determined by spectroscopic methods. Compounds 1-5 are 6,7-seco-ent-kaurane-7,20-olide diterpenoids, and 6-12 bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 1 publication
0
63
0
Order By: Relevance
“…laxiflora, and its structure was confirmed by NMR and single-crystal X-ray diffraction in 2002. 15 The molecular formula of compound 4 was determined to be (Figure 3) (for the observed proton spin systems, H-9/H 2 -11/H 2 -12/H-13/H 2 -14, H 2 -1/H 2 -2/H 2 -3, and H-5/H 2 -6/H-7) confirmed this result. Based on detailed analysis of ROESY data, the relative configuration of the stereogenic centers in compound 4 were determined to be the same as those in laxiflorin O (5).…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…laxiflora, and its structure was confirmed by NMR and single-crystal X-ray diffraction in 2002. 15 The molecular formula of compound 4 was determined to be (Figure 3) (for the observed proton spin systems, H-9/H 2 -11/H 2 -12/H-13/H 2 -14, H 2 -1/H 2 -2/H 2 -3, and H-5/H 2 -6/H-7) confirmed this result. Based on detailed analysis of ROESY data, the relative configuration of the stereogenic centers in compound 4 were determined to be the same as those in laxiflorin O (5).…”
Section: Resultsmentioning
confidence: 64%
“…The analysis of the 13 C NMR and DEPT spectra (Table 2) revealed the presence of 24 carbons, which were assigned as three methyls (δ C 29.9, δ C 24.1, and δ C 29.7), six methylenes (one oxygenated at δ C 65.6), seven methines (one oxygenated at δ C 73.5 and two olefinic groups at δ C 127.4 and δ C 160.7), and eight quaternary carbons (one hemiacetal at δ C 96.3 and four carbonyls at δ C 197.4, δ C 225.2, δ C 207.5, and δ C 206.1), which suggested that 1 is a highly oxygenated diterpenoid with a C 24 skeleton similar to the ent-kaurane skeletons previously reported. 4,9 Comparison of the NMR spectral data of 1 with those of eriocalyxin B (6) 16 revealed that 1 was consistent with *To whom correspondence should be addressed. E-mail: pujianxin@mail.kib.ac.cn (J.X.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Briefly, cells were placed in 96-well plates 12 h before treatment with initial density of 5000 cells/well and continuously exposed to different concentrations (40, 8, 1.6, 0.32, and 0.064 mol.L -1 ) of compounds for 48 h, with cisplatin (Sigma, USA) as the positive control. Inhibition rates of cell proliferation after compound treatment were determined by MTT assay, as described previously (Niu et al, 2002;Monks et al, 1991), and IC 50 calculated with Reed and Muench method (Reed and Muench, 1938).…”
Section: Cytoxicity Assaymentioning
confidence: 99%